Alcohol use during the COVID-19 pandemic in Latin America and the Caribbean - Rodrigo Garcia-Cerde; Juliana Y. Valente; Ivneet Sohi; Rachael Falade; Zila M. Sanchez; Maristela G. Monteiro (Pan American Health Organization, 2021)
Objective. To assess the association between drinking behaviors during the COVID-19 pandemic and quarantine, anxiety symptoms, and sociodemographic characteristics in Latin America and the Caribbean (LAC). Method. Data was collected through a cross-sectional online survey (non-probabilistic sample) conducted by the Pan American Health Organization between May 22 and June 30, 2020, in 33 countries and two territories of LAC. Participants were 18 years of age or older and must not have traveled outside of their country since March 15, 2020 (n= 12 328, M age= 38.1 years, 65% female). Four drinking behaviors (online socializing drinking [OSD], drinking with child present [DCP], drinking before 5 p.m. [DB5]), heavy episodic drinking [HED]) were response variables, and quarantining, anxiety symptoms and sociodemographic covariables were explanatory variables. Results. Quarantine was positively associated with a higher frequency of OSD and with DCP, but negatively associated with a higher frequency of HED. Anxiety symptoms were associated with a higher frequency of HED, more OSD, and DB5. Higher incomes seemed to be more associated with all the studied drinking behaviors. Women tended to report less DB5 and less HED during the pandemic. Conclusions. Quarantine during the COVID-19 pandemic seems to affect drinking behavior and mental health indicators like anxiety symptoms. This study is the first effort to measure the consequences of the quarantine on alcohol consumption and mental health in LAC during the COVID-19 pandemic. Considering the associations found, screenings and brief interventions targeting alcohol consumption and mental health are recommended.